Apuntes sobre el proceso constituyente en Chile - Zegarra Llanos, Irene Jetsabel (2022)
In October 2019, in Chile, a series of protests and demonstrations took place, which promoted the constituent process in that country. As a result, the Constitutional Convention was formed, a body that, after a year of work, created a new constitutional text that will be voted on through a constitutional plebiscite to be held in September of this year. In this context, the purpose of this interview is to analyze and evaluate the most important aspects of the constitutional process.